2019
DOI: 10.1017/s0272263119000536
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency as a Mediating Variable of Intelligibility for Different Varieties of Accents

Abstract: Factors that affect comprehension of accented English (e.g., Harding, 2011) have been well studied, but little research examines how listeners’ proficiency affects their sensitivity to second language (L2) accent. The current study investigated the effect of test takers’ English proficiency on their comprehension ratings and ability to correctly transcribe different World Englishes accents. Ten speakers from six countries with different L1 backgrounds (i.e., North American, British, Indian, South African, Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Based on a large-scale experimental study, it shows that nonnative listeners at different levels profit from various types of co-textual and contextual cues when recognizing words spoken with another nonnative accent. Its findings highlight the need for a greater recognition of co(n)textual factors and listening proficiency as relevant variables in research on international intelligibility, both of which have so far received relatively little attention in the field (see also Kang, Moran, et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Based on a large-scale experimental study, it shows that nonnative listeners at different levels profit from various types of co-textual and contextual cues when recognizing words spoken with another nonnative accent. Its findings highlight the need for a greater recognition of co(n)textual factors and listening proficiency as relevant variables in research on international intelligibility, both of which have so far received relatively little attention in the field (see also Kang, Moran, et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Another line of research focused on the intelligibility of accents ( Kang et al, 2018a , b , 2020 ). Intelligibility refers to the extent to which the speakers’ intended utterance is understood by listeners, which is generally measured by transcription tasks ( Kang et al, 2018a , b ).…”
Section: Resultsmentioning
confidence: 99%
“…Kang et al (2018b) examined the relationship between the phonetic/phonological features of speakers and intelligibility, which helps test developers to select speakers with different English accents for listening input. More recently, Kang et al (2020) examined the relationship between test-takers' proficiency levels and comprehension of different accents. They found that test-taker's proficiency levels affected their comprehension of accented speech, and the performance of intermediate-level test takers, whose TOEIC scores were between 305 and 400 (i.e., 61-80th percentile), was more sensitive to speech with different accents than the beginner and advanced groups.…”
Section: Speakersmentioning
confidence: 99%
“…For instance, Kang and Kevin Hirschi (with Helmer Strik and Catia Cucchiarini at Radboud University, John Hansen at the University of Texas-Dallas, and Keelan Evanini at the Educational Testing Service) are currently developing an affective interactive oral communication tutor for limited English proficiency populations. Using the 2019 IELTS joint research fund, Kang (with Seoul National University's Hyunkee Ahn and NAU's Meghan Moran and Katherine Yaw) is also applying such tools to a project analyzing the linguistic progression of Korean adult learners of English who are preparing for the IELTS (Kang et al, 2018a, 2018b, 2019; Kang et al, forthcoming). In an additional study involving speech analysis, alumna María Nelly Gutiérrez Arvizu (Universidad de Sonora) is investigating fluency features in Spanish-speaking kindergarten learners of English.…”
Section: L2 Speechmentioning
confidence: 99%